Why Do Rice Millers Refuse to Partner With the State? A Socio-Agronomic Perspective From Indonesia’s Agricultural Heartland - Simanjuntak, Kartika Damayanti; Chalil, Diana (Baileo: Jurnal Sosial Humaniora, 2025)
This study aims to analyze the factors influencing rice millers’ willingness to engage in partnership with the Indonesian State Logistics Agency (Bulog) in Serdang Bedagai Regency, North Sumatra—one of the region’s key rice production centers. Despite this status, participation in Bulog’s procurement partnership scheme remains low. Employing a quantitative approach, this study involved 13 rice milling enterprises across six districts. Variables analyzed include Bulog’s outreach (socialization), purchase price, production capacity, market certainty, and business longevity. Data were examined using Fisher’s Exact Test due to the small sample size and categorical data type. Findings reveal that only the socialization variable had a statistically significant effect on partnership willingness. Bulog’s efforts in providing detailed information, explaining partnership schemes, and maintaining intensive communication played a crucial role in encouraging participation. In contrast, non-competitive pricing, varying production capacities, market stability, and business duration showed no significant effect. This study contributes to the socio-agribusiness literature by highlighting the importance of institutional communication in fostering state–private partnerships in the food sector. Key recommendations include enhancing the frequency and quality of Bulog’s outreach, improving procurement pricing mechanisms, and promoting local government support to strengthen rice supply chain integration through more inclusive partnership models.